Efectos jurídicos y sociales de la responsabilidad patronal en los accidentes de trabajo ante los procesos tramitados en la Unidad Provincial del riesgo de trabajo del IESS de la ciudad de riobamba durante el año 2012. - Lemache Vallejo, Leonor Alexandra (2016)
Throughout the history of our Ecuadorian law had developed several views on the right to social security, and how this right has been based on these guiding principles for proper satisfaction of all persons protected by this constitutional right. As had perfected public policies with which the Ecuadorian Institute of Social Security for several years been implemented for proper operation. As it is so for determining certain employer responsibility for industrial accidents that take place daily by the activities performed by workers who are at risk for their work for companies or factories, has made regulations for each case explicitly and does not cause an error when determining the loss. The responsibility lies not only in companies or factories that handle this type of work at risk to their workers, but rather employer who for various reasons is under a responsibility criteria adopted by the Ecuadorian Institute of Social Security because you can set an accident of work this will not only be determined within working hours and included the hours since the move from home to your workplace occur, so that on several occasions such events increases accidental relationship of the worker with the company, but the employer's liability is expressed by certain actions carried out or not by the employer for the Ecuadorian Institute of Social Security, which the proper provision of services that this institution has for workers who duly this affiliated. While the lack of liability by the employer does not affect the immediate attention in the event of an accident at work and assistance that can be provided to the employee, but the employer will establish a penalty for failure of its obligations to the Ecuadorian Institute of Social Security, in order to determine the employer or liability, the institution subsidies needed to affiliate their families in case of permanent disability, orphans and widows. Workers from the case has suffered an accident, this should be immediately reported to the Ecuadorian Institute of Social Security, the same through its website, a number of requirements for the same, after which, it takes a thorough investigation of the incident reported to the institution, setting certain parameters for this, the Ecuadorian Institute of Social Security takes first documentary and testing procedure actually is affiliated and current on their contribution to the facade of the accident, and then based on medical descriptions to determine having suffered an accident, When some kind of liability is established by the employer, it must comply with an imposed sanction, which not comply will be punished with employers blackberry and in the absence of immediate payment Ecuadorian Institute of Social Security by coercive action will be effective payment of the benefit to be met by employer, thus causing far-reaching legal consequences for the employer in view affects their legal situation.